P7 De novo bronchiectasis in people with haematological malignancy. (December 2018) - Jose, RJ; Hall, JI; Brown, JS
Abstract : Introduction: Bronchiectasis is increasingly recognised as a complication of haematological malignancy, but the risk factors for the development of bronchiectasis in this population are poorly understood, and factors associated with survival are unknown. Methods: Data (haematological, respiratory and radiological characteristics, and mortality) were collected from the records of patients with haematological malignancy and clinical bronchiectasis attending a UK teaching hospital bronchiectasis clinic. Multiple imputation was used for missing lung function values in regression analyses. Odds ratios (OR) and hazards ratio (HR) were adjusted for age, haematological malignancy and stem cell transplantation (SCT). Results: Seventy five patients were identified. The mean (SD) follow up time from bronchiectasis diagnosis was 1363 (1155) days. None had bronchiectasis at the time of haematological malignancy diagnosis. Patient characteristics are detailed in table 1. IgG deficiency (<7 g/L) was significantly associated with rituximab administration (OR 4.73 (95% CI 1.76 to 12.70, p=0.002)). Pulmonary graft-versus-host disease (GVHD) was associated with bronchiectasis in ≥3 lobes at presentation (OR 6.72 (95% CI 1.23 to 36.58, p=0.028) and lower mean (SEM) FEV1% (61.3 (6.6) vs 80.9 (3.7)), p=0.003) and FVC% (77.8 (5.3) vs 91.7 (3.5), p=0.018). Twelve (16%) patients were colonised with bacterial pathogens and had lower mean (SEM) FEV1% (56.4 (8.3) vs 79.1 (3.8), p=0.012). Seven (58%) were colonised with Pseudomonas aeruginosa . Survival at 1, 5 and 10 years was 82%, 65% and 59%, respectively. Mortality was associated with age (OR 1.07 (95 CI 1.02 to 1.13, p=0.012) and FEV1% (OR 0.93 (95% CI 0.88 to 0.98, p=0.011). Survival time was associated with age (HR 1.07 (1.03–1.12), p=0.003), FEV1% (HR 0.95 (0.93–098, p=0.000), bacterial colonisation (HR 3.31 (1.12–9.79, p=0.030), and SCT (HR 3.94 (1.03–15.14), p=0.046). Conclusion: Bronchiectasis arises de novo in patients with haematological malignancy. Mortality was significant and we advise a high index of suspicion for the detection of bronchiectasis in patients with haematological malignancy as early diagnosis, maintaining lung function and reducing the risk of colonisation may offer a survival benefit, particularly in those undergoing SCT.